UJI ADAPTASI VARIETAS UNGGUL BARU PADI MELALUI PENGELOLAAN TANAMAN TERPADU - Aryawati, Sagung Ayu Nyoman; Kamandalu, Anak Agung Bagus; Suastika, Ida Bagus Kade; Sunanjaya, Wayan; Sari, Anella Retna Kumala (Agropross : National Conference Proceedings of Agriculture, 2022)
Variety is one of the important components that contribute to increasing rice productivity and farm income. The purpose of the study is to obtain high productivity adaptive VUB and increase farmers' income to support organic farming. The study was conducted in Subak Timpag, Kerambitan, Tabanan, Bali Province in 2017 covering an area of ​​4 hectares using organic fertilizer PTT technology. The varieties used were Inpari 19, 24, 30, 31, 32, 33, and Mekongga as comparison. The variables observed were the components of growth, yield, and farming. Data were analyzed using ANOVA, single factor RAK with seven varieties as treatment with 10 replications. Farming costs and income were analyzed using income analysis and financial feasibility. The results of statistical analysis of several VUB treatments had a very significant effect on some growth and yields. VUB that can adapt well are Inpari 30, 19 and 31 varieties with a productivity of 7.87; 7.30 and 6.85 tons/ha. The average productivity increase is 1.64 tons/ha GKG or an increase of 29.88%. The results of the analysis of the costs used increased by 11.88%, but revenues also increased by 23.11% so that the average increase in income was 34.97% or Rp. 3,400,000.00 per ha, with an increase in the R/C ratio before and after assistance of 0.20 or 10.03%. The application of PTT technology is able to increase lowland rice productivity and can economically increase rice farming income, to support organic agriculture in Bali Province.